Optimization of the geometry and the turbine induced damping for fixed detached and asymmetric OWC devices: A numerical study. (15th November 2017) - Simonetti, I.; Cappietti, L.; Elsafti, H.; Oumeraci, H.
Abstract: This paper presents the set-up, the validation and the application of a two-phase incompressible three-dimensional Computational Fluid Dynamic (CFD) model for an extensive parameter study on the performance of a fixed, detached Oscillating Water Column (OWC) wave energy converter. The numerical study aims to assess the combined effect of relevant design parameters (chamber length, front wall draught, damping applied by the turbine) and of the wave conditions (wave height, wave period and water depth) on the device performance, with reference to its hypothetical installation in moderate wave climates (e.g. in the Central Mediterranean Sea). The OWC device examined here is fixed, detached from the seabed, and with asymmetric front and back walls as a characteristic feature. The results show that, by appropriately tuning the design parameters, a maximum value of the capture width ratio of approximately 0.87 can be achieved. Highlights: A parameter study on the performance of an OWC device is performed. Reference wave conditions are those of moderate wave climate (central Mediterranean areas). The device is modelled by using Computational Fluid Dynamics. The results outline a strong mutual interaction of design parameters on the performance. A maximum capture width ratio up to 87% can be achieved for the optimized device.